Symbolic Interaction Of Nonverbal Communication In Volleyball (Case Study on the Volleyball Team of Rimbo Kedui Village, Seluma Selatan District, Seluma Regency) - Apriani, Deri; Yanto, Yanto; Risdiyanto, Bayu (Utami Publisher, 2025)
Nonverbal communication is a way of communication commonly used in various activities. There are many ways to communicate something by using symbols, codes, and images. In the volleyball game conducted by the Rimbo Kedui team, communication occurred between the coach and the players. The usual communication method used is through finger codes and body movements. These finger codes have specific meanings that can only be understood by fellow players. The symbolic interaction theory used in this research is Herbert Mead.Nonverbal communication is also used in a volleyball game, one form of nonverbal communication widely used by setter Rimbo Kedui is hand signals to inform the pass that will be given to the smasher, in addition to hand signals, another nonverbal form is eye contact, but its intensity is not as much as using hand signals, such as clenching hands, thumb and index finger, five fingers, and many more. By using the attack codes arranged by the setter, it becomes more secretive because only their teammates understand those codes.